Different relational models have shaped the biocultural conservation over time of Araucaria araucana forests and their people - Ladio, Ana Haydee (2023)
For the Mapuche people, Araucaria araucana, which is known as “Pewen” in Mapudungum, Mapuche language, is a cultural keystone species. Evidence shows that the species has been part of the food sovereignty of the Pewenche (Pewen people in Mapudungun) and their ancestors since 3000 BP. The Pewen landscape has held a strong material and symbolic significance for the Mapuche communities since before Europeans arrived in the region. The concept of relational models (RMs) provides a framework that contributes to the spatial–temporal pattern analysis of the use of Pewen by people through time. This framework involves a set of preferences, principles, and virtues that explain the degree of responsibility toward nature that different cultural groups have developed. This chapter describes and analyzes RMs that have prevailed on Pewen forest management, based on bibliographical sources in the fields of archeology, historical ecology, ethnohistory, and ethnobotany. The RMs of domination, exploitation, custody, and mutual nurturing provide clues to understanding human–Pewen forest relationships and vary over time and sociocultural contexts, as colonial processes and their neo-colonial legacies have shaped the fate of the conservation of these forests and their native inhabitants. The results herein show that the RM of mutual nurturing of Pewenche communities is a model that has an indispensable ethic for building resilience in contexts of socio-environmental change.